The impact of cataract surgery upon visual acuity and quality of life in patients with cataract in Tripura - Acharya, Monali; Baidya, Subrata; Das, Rituparna; Sarkar, Phani; Choudhury, Himadri (International Journal Of Community Medicine And Public Health, 2020)
Background: The major cause of blindness in India is cataract. Blindness leads to poverty due to reduced productive activity and this leads to reduced quality of life. This study was aimed at evaluating the visual acuity (VA) change pre and post cataract surgery, the post-surgical quality of life (QOL) outcomes and level of satisfaction estimation. Methods: This was a cross sectional, hospital based study carried out in a tertiary care centre in Tripura. It included 200 patients over a period of 1.5 years to compare the VA, QOL, psychosocial status and satisfaction level pre and post cataract surgery. Indian vision function questionnaire 33 (INDVFQ33) was used to assess QOL. Results: Out of 200 patients, in 53% preoperative VA ranged from >20/400 - <20/200 while in 5% patients it was only perception of light. Postoperatively 80% of the patient achieved best corrected VA (BCVA) of 20/30 or better, 18% patient attained BCVA ranging from 20/40 to 20/60. Only 2% had a BCVA of 20/60 or worst. QOL parameters like mean pre and post -operative general function score, psychosocial scale and visual function scale showed improvement following cataract surgery. 69% of the patients were satisfied with the cataract surgery, whereas 31% were not completely satisfied. Conclusions: The study revealed that there was a marked improvement in VA post cataract surgery and it also influenced the QOL in all scales.